PENGEMBANGAN SISTEM UJIAN YANG BERKELANJUTAN UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI KELAS - Fitriah, Nurlaeli (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
Improved quality of learning in education can be done in many aspects. One way is to approach the evaluation of student learning, in this case to optimize the system testing performed on an ongoing basis. In practice, the examination system to achieve exhaustiveness continuous learning by the students, but in its development does not stop in that area alone, this system allows teachers to conduct follow-up evaluation for themselves teachers in self-evaluation framework for the development of edukasinya activity.Key words: exam system, quality of learning